Optimization and Simulation of a Reasonable Scheduling Model under Multiple Tasks in Company Management - Zhuo Wang (Complexity)
With the rapid development of market economy, the task scheduling model has become the core problem in the field of corporate management. In order to solve the problem that the stability of the model will decline due to the interference of human factors in the process of multitask scheduling in the traditional algorithm, a reasonable scheduling model based on the priority principle is proposed in this paper. This paper expounds the principle of multitask scheduling in company management, constructs a multitask scheduling network model based on priority, performs virtual scheduling on the model, searches the optimal solution in the solution space of the scheduling problem, and obtains the reasonable multitask scheduling method in the company management. Through the analysis of relevant simulation experiments, it can be concluded that the task scheduling algorithm proposed in this paper can not only allocate the corresponding resources for high-priority tasks effectively, but also can save the cost, so as to show better execution efficiency.